(untitled) (Global Journal of Science Frontier Research, 2019)
Soil microbial biomass and microbial metabolic quotients have been identified as the most effective indicators of a response to ecosystem development and disturbance. In order to determine the effects of grassland restoration programs, we analyzed the distribution of soil microbial parameters in different aggregate fractions at 1yr, 10 yr. and 30 yr. Results show that C mic and P mic increased with grassland succession, the greatest values were concentrated at a micro-aggregate size. However, qCO 2 decreased as the years under restoration increased. qCO 2 was significantly correlated with SOC, TN, P mic (negatively) and C mic (positively). Natural succession of grassland alters soil microbial properties positively, which plays a major role in aggregate formation. The time under vegetation rehabilitation impacts soil microbial parameters at different aggregate sizes, especially for qCO 2 where 2-3 mm was found to be the aggregate size that was least influenced by soil quality.